Construction of rice drought cDNA library and identification of NLI-IF1 using yeast one hybrid screening - Phuong, Nguyen Duy; Tu, Tran Tuan; Hoi, Pham Xuan (Academia Journal of Biology, 2012)
Rice database search on promoter sequences revealed a target sequence (CCTCCTCC) that commonly appears on stress inducible promoters of functional genes involved in abiotic stress, such as, drought, high salt and cold. In addition, promoter analysis of two stress inducible promoters, it shows that JRC0332 express specifically in cold stress and JRC0528 in ABA, high-salinity, drought and cold stresses respectively and both promoters contain the target sequence. In this study, we construct a drought cDNA library from total RNA of Niponpare variety for gene screening. Yeast one-hybrid screening technique using two target sequences of 50 nucleoties on JRC0528 and JRC0332 promoters contain the target sequence for drought cDNA library screening. We identify a cDNA encoding a Nuclear LIM interactor-interacting factor (NLI-IF1). In-vivo specific binding in Yeast suggested that NLI-IF1 bind specifically to the target sequence